2018
DOI: 10.1080/10826084.2018.1461225
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits in a Cohort of Persons with Substance Use: Incorporating the Role of Social Networks

Abstract: Background Frequent emergency department (ED) visits often suggest inappropriate use for low acuity needs and multiple comorbidities, including substance use disorders. Objective This study examines associations of individuals and their social networks with high frequency ED use among persons reporting substance use. Methods Information was obtained from interview responses from the first 6-month follow-up visit of a longitudinal. Prevalence ratios for the outcome of high frequency ED visits (≥2 in 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As a component of social support, informational support has been linked to improve emergency healthcare utilization 28‐30 and progress through the HCV care continuum among people who use drugs 29 . Similarly, having specific network members, such as supportive family members, has been linked to different stages of the HCV care continuum, including HCV treatment initiation and achievement of HCV cure 39,42,43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a component of social support, informational support has been linked to improve emergency healthcare utilization 28‐30 and progress through the HCV care continuum among people who use drugs 29 . Similarly, having specific network members, such as supportive family members, has been linked to different stages of the HCV care continuum, including HCV treatment initiation and achievement of HCV cure 39,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on social network theory, through group or individual relationships, network members, or peers, provide critical functional social support to one another. Among different levels of support, informational support consists of sharing knowledge, offering suggestions or giving advice, and has been previously linked to healthcare utilization within populations of PWID 27‐30 . Modelling data on HCV transmission and elimination support the importance of considering PWID social network factors in intervention development and its potential impact on reducing overall HCV incidence 31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the concept of low threshold was expanded in this study, as a result of our consultations, to include a reduction in expectations and stigma of emergency response providers toward people experiencing homelessness and PSU. This need stems from the extent of stigma experienced by people with these dual issues while seeking help or using emergency services (Alunni-Menichini et al, 2020;Doran et al, 2014;Lang et al, 2013;Sacamano et al, 2018;Wise-Harris et al, 2017).…”
Section: B Low Thresholdmentioning
confidence: 99%
“…1 Persons with substance use disorders and other comorbid conditions, such as mental illness or homelessness, commonly seek care in ED settings, often as a result of lack of access to regular sources of primary and specialty care. [2][3][4] Frequent hospital and ED use has been linked to greater risk of experiencing both nonfatal and fatal overdoses, 5,6 and both US and international research has found ED utilization to be highest in the months preceding and after overdose. [7][8][9] Given that persons at risk of overdose interact frequently with the ED, intervening at this point of contact could be an effective overdose prevention strategy.…”
Section: Introduction Backgroundmentioning
confidence: 99%